Nodopathies in the Early Diagnosis of Axonal Forms of Guillain-Barré Syndrome - Urdiales-Sánchez, Sara; González-Montaña, José-Ramiro; Diaz-Pérez, Ricardo; Calvo-Calleja, Pablo; Gutiérrez-Trueba, María-Antonia; Urdiales-Urdiales, Javier (Frontiers in Neurology, 2022)
Introduction: Guillain-Barré syndrome (GBS) has been classified into demyelinating and axonal subtypes or forms, including Acute motor axonal neuropathy (AMAN) and regional pharyngeal-cervical-brachial variant (PCBv). Objective: To study the relationship between motor nerves conduction blocks (CBs) and prognosis in AMAN and PCBv. Patients and methods: We retrospectively analyzed six cases of AMAN and PCBv with serial nerve conduction studies (NCS) and electromyography (EMG). Results: The serial NCS (1st-2nd, 3rd week) showed, as the most constant data, a decreased amplitude of the Compound Muscle Action Potential (CMAP) in 100/% of cases. CBs were present in 66.6% of cases. EMG (3rd week) showed signs of severe denervation in 33.3%. All patients were treated from the 1st-2nd week of evolution with intravenous immunoglobulins. Patients with CBs (1st-2nd, 3rd week), showed reversible CBs or reversible conduction failure (RCF) and complete recovery at 1 month. Patients without CBs, with persistent reduced distal CMAP amplitude (dCMAP) showed severe acute denervation due to axonal degeneration (3rd week and 1st-3rd month) and slow recovery of several months. Conclusions: Not all axonal forms of GBS have a poor prognosis. This study of AMAN and PCBv, shows that patients with CBs can have reversible CBs or RCF, and good prognosis. Patients without BCs, with persistent reduction of dCMAP amplitude decrement, have severe acute denervation, and worse prognosis. AMAN and PCBv have a continuous spectrum ranging from CBs due to dysfunction/disruption of Nodes of Ranvier, called Nodopathies, with reversible CBs or RCF and good prognosis, to axonal degeneration with worse prognosis.